DEVELOPING SPEAKING MEDIA IN TEACHING DESCRIPTIVE TEXT THROUGH SCRATCH PROGRAM FOR SEVENTH GRADE STUDENTS AT SMPN 27 MEDAN - Poppy Shania M. Sihombing; Safrida Lubis (Universitas Negeri Medan, 2022)
This study aims to develop speaking media in teaching descriptive text through Scratch Program for seventh grade students at SMPN 27 Medan. This study was conducted by using Research and Development model (R&D) by Borg and Gall (2003) which is simplified into six stages or procedures by Puslitjaknov (2008). The procedures are gathering data and information, analyzing the data, designing media, validating by expert, revising media and final product. The subject of the study was seventh grade students at SMPN 27 Medan. Meanwhile, the study was conducted in class VII-1 that consist of 32 students. The data were collected through a questionnaire. The purpose of using a questionnaire is to extract data from respondents. The developed speaking media was assessed and judged by two experts. The experts are an English lecturer from Universitas Negeri Medan and an English teacher from SMPN 27 Medan. The result data of experts’ validation of speaking media in teaching descriptive text through Scratch Program, the average score of media validation is 95,19%. From the validation, this media got excellent criteria. The media was appropriate to be used by seventh grade students at SMPN 27 Medan. The media is suitable with their needs to make them more attract in studying descriptive text.Key words: Research and Development (R&D), Speaking Media, Descriptive Text, Scratch Program, Seventh Grade Students.